2018
DOI: 10.1016/j.appet.2018.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Goal-setting and volitional behavioural change: Results from a school meals intervention with vitamin-A biofortified sweetpotato in Nigeria

Abstract: Malnutrition, particularly vitamin A deficiency, is a major public health problem in many developing countries. This study investigated whether priming or self-generation of goals, or whether attention to instrumental or experiential goals together with use of a reminder condition or not, promotes dietary behaviour intentions and change. A set of 556 randomly selected children aged 7–12 in Osun state, Nigeria, participated in an four-week intervention and field experiment in which a meal based on orange-fleshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Nutrition behaviour. Of the seven studies (34,42,44,(47)(48)(49)(50) on this outcome, only two (47,48) reported a positive impact of SBNI on nutrition behaviour. Improvement in nutrition behaviour such as less sugar intake or more consumption of fruits and vegetables was primary measures in studies that assessed this outcome.…”
Section: Intervention Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…Nutrition behaviour. Of the seven studies (34,42,44,(47)(48)(49)(50) on this outcome, only two (47,48) reported a positive impact of SBNI on nutrition behaviour. Improvement in nutrition behaviour such as less sugar intake or more consumption of fruits and vegetables was primary measures in studies that assessed this outcome.…”
Section: Intervention Effectsmentioning
confidence: 97%
“…Interventions that were evaluated in our analysis were mainly school-based nutrition programmes focusing on supplementation of school meals with micronutrients and/or assessment of the effects of micronutrients on nutrition status of schoolchildren (36)(37)(38)42,43,45,46) . Others assessed the impact of school nutrition education with/without physical activity programmes on nutrition knowledge, dietary intake patterns and nutrition status (34,44,(47)(48)(49) . Some papers also focused on promoting healthy dietary choices (36,38,42,44,48,49) .…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations